“Like the Name of a Well-Known Chapter in Tractate Ketubot”: Outrages in the Rabbinic Hebrew of Y.H. Brenner’s Around the Point - Sharp, Orel (MiKAN, 2022)
The article examines Brenner’s approach to the historical rabbinic Hebrew dialect and the understanding of its unique virtues in terms of the ability to discuss sexuality and taboo issues. Brenner’s stance is reflected in the indirect Talmudic references he uses to describe the criminal sexual deeds of Shneiser, a character in the novel. This approach also appears in the indirect mishnaic language Brenner uses to describe the sexual atrocities that take place in Katzman’s house. The narrator in Around the Point refrains from overly explicit descriptions of the incest that takes place between Katzman and his daughter, which is hinted at only behind the veil of rabbinic idioms; even in the original texts, these are only insinuations. However, the narrator does not hide the camivalesque experience when describing Katzman’s house. Discussing these examples, the article attempts to understand the linguistic approach Brenner seeks to preserve regarding sexuality and taboo issues.